2008
DOI: 10.1177/0363546508324178
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Subtle Residual Shoulder Symptoms after Transtendinous Arthroscopic Cuff Repair

Abstract: Arthroscopic transtendon partial articular supraspinatus tendon avulsion-type rotator cuff repair was a reliable procedure that resulted in a good outcome in terms of pain relief and shoulder scores in 98% of the 54 patients. Better results could be expected in patients with less tendon retraction, a larger footprint exposure, of younger age, and with a clinical history of trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 34 publications
4
58
0
1
Order By: Relevance
“…Complete removal of the cuff insertion makes also it difficult to anatomically repair the lesion and restore the native tendon footprint, resulting in biological and mechanical flaws. In transtendon repair, extensive retraction of the tendon may excessively medialise the cuff insertion, and alter both anatomy and mobility of the joint [7]. Pulling a retracted articular layer onto the original footprint may over-tighten the bursal aspect and, consequently, unbalance the tension in the remaining fibres [16], which may explain why transtendon repair is alleged to be more painful, take longer to recover, and be more likely to develop shoulder stiffness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete removal of the cuff insertion makes also it difficult to anatomically repair the lesion and restore the native tendon footprint, resulting in biological and mechanical flaws. In transtendon repair, extensive retraction of the tendon may excessively medialise the cuff insertion, and alter both anatomy and mobility of the joint [7]. Pulling a retracted articular layer onto the original footprint may over-tighten the bursal aspect and, consequently, unbalance the tension in the remaining fibres [16], which may explain why transtendon repair is alleged to be more painful, take longer to recover, and be more likely to develop shoulder stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Debridement, with or without acromioplasty, was advocated [2,3], but the current trend is to repair lesions involving more than 50 % of the tendon thickness, or exceeding 6 mm (Grade 3) of depth [4]. The present evidence favours conversion from partial into full thickness, and repair of the tear in a traditional fashion [5,6], or a trans-tendon repair [7,8]. Both techniques are effective in functional recovery and relief of symptoms, but controversy persists because of the lower morbidity rate and earlier recovery when completing and repairing tear, whereas tendon integrity, native footprint, and biomechanical properties (gapping and mean ultimate failure strength) are better restored when performing a transtendon repair, leaving the bursal side intact [9,10].…”
Section: Introductionmentioning
confidence: 89%
“…The transtendon repair technique allows restoration of the medial side of the footprint while also maintaining the bursal layer of the torn cuff. 15,16 Castagna et al 7 have linked the effectiveness of the transtendon repair technique to decreased tendon retraction, large footprint exposure, younger patients, and a clinical history of trauma. According to another study, the transtendon repair technique reduces pain.…”
Section: E590mentioning
confidence: 99%
“…4 The most recent debate is inclined toward the conversion from a partial-to full-thickness tear and repair of the tear 5,6 or transtendon repair. 7,8 Both methods result in functional recovery and relief, but repairing the tear results in lower morbidity and earlier recovery whereas the tendon integrity, native footprint, and biomechanical properties (gapping and mean ultimate failure strength) are better in the case of transtendon repair, which keeps the bursal side intact. 9 The transtendon repair techniques described so far involve some challenges in surgical implementation and require experience.…”
mentioning
confidence: 99%
“…15 Other studies have supported the idea that transtendinous techniques result in a lower rate of failure while suggesting that the functional outcomes and patient satisfaction after transtendinous repair may be higher than previously thought. 16,17 One study found 1 failure and good to excellent results in 93% of cases at 12 years' follow-up of PASTA lesions repaired with a transtendinous technique. 16 We developed a novel inside-out repair technique for partial articular surface supraspinatus tears.…”
mentioning
confidence: 99%